Precision calorimetry for power loss measurement of a very low power maximum power point tracker - Wolfs, Peter; Li, Q. (Curtin University, 2007)
Efficiency is an important performance measure for DC-DC converters. Its measurement can be extremely difficult when the DC-DC converter is highly efficient and the power loss is extremely low. The input and the output waveforms of a high frequency dc-dc converter may have high frequency components superimposed on the DC components. This further complicates the measurement process as some digital instruments tend to misbehave. Calorimetry method has been previously proposed as an alternative and indirect power loss measurement method. This paper proposes an improved calorimetry method which is capable of resolving the power loss below 2 mW. The method is demonstrated for a single-cell maximum power point tracker with a power rating of 650 mW. The experimental results confirm that the device under test presents a power loss of 24 mW +1.3 mW and the converter achieves an efficiency of 96.2% + 0.2%.